(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Endoscopic cholecystectomy is a routine surgical treatment of gallbladder stones. Endoscopy is less invasive than open surgery, but the incidence of postoperative nausea and vomiting is higher than open surgery, about 40-70%. The prophylactic efficacy of Ondansetron for postoperative nausea and vomiting has been demonstrated through numerous studies. Dexamethasone is an easy-to-find and cheap drug, but has not been widely used in the prevention of nausea and vomiting after surgery. Research objects and methods: Randomized clinical intervention study with control group, single blind. Comparison of nausea - vomiting prophylaxis efficacy of Dexamethasone and Ondansetron in the first 24 hours after laparoscopic cholecystectomy in 208 patients. Group D (Dexamethasone) 105 patients received 4 mg of Dexamethasone intravenously upon induction, Group O (Ondansetron) 103 patients received 8 mg of Ondansetron intravenously upon induction. All patients received postoperative care and treatment according to the same protocol. Patients were assessed for postoperative nausea - vomiting during the first vomiting period. Monitor for vomit prevention medicine side effects such as headache, dizziness... Results: Nausea - vomiting prophylaxis effect of Dexamethasone and Ondansetron in the first 24 hours after laparoscopic cholecystectomy, postoperative nausea-vomiting rates of patients undergoing laparoscopic cholecystectomy with one or more risk factors according to Apfel, in the group prophylactic with Dexamethasone 4 mg, 16.5% compared to the group prophylactic with Ondansetron 8 mg, 20%, were similar. Conclusions: The nausea - emesis prevention effect of Dexamethasone 4 mg and Ondansetron 8 mg in the first 24 hours after laparoscopic cholecystectomy is almost the same.